2002
DOI: 10.1055/s-0037-1613033
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine Reverses Platelet Activation Induced by Human IgG Antiphospholipid Antibodies

Abstract: SummaryProthrombotic properties of antiphospholipid (aPL) antibodies may be explained in part by their ability to enhance the activation of platelets pre-treated with low doses of ADP or thrombin. The antimalarial drug hydroxychloroquine (HQ) has been used successfully in prevention of postoperative thrombosis and in treatment of patients with SLE or APS. In one study, administration of HQ reversed the thrombogenic properties of aPL in mice. However, the mechanism of action of HQ in preventing thrombosis is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
151
0
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(157 citation statements)
references
References 30 publications
1
151
0
5
Order By: Relevance
“…Moreover, aPL have been shown to increase production of TXB 2 in the presence of low doses of ADP, collagen, or thrombin (7,10,26,27). A recent study by our group showed a significant increase in the expression of activated glycoprotein IIb/IIIa on platelets treated with aPL and TRAP (8). Furthermore, aPL-enhanced thrombosis in vivo can be abrogated by infusions of a glycoprotein IIb/IIIa antagonist (1B5) monoclonal antibody and in ␤ 3 -null (glycoprotein IIb/IIIa-deficient) mice (Vega-Ostertag M, et al: unpublished observations).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, aPL have been shown to increase production of TXB 2 in the presence of low doses of ADP, collagen, or thrombin (7,10,26,27). A recent study by our group showed a significant increase in the expression of activated glycoprotein IIb/IIIa on platelets treated with aPL and TRAP (8). Furthermore, aPL-enhanced thrombosis in vivo can be abrogated by infusions of a glycoprotein IIb/IIIa antagonist (1B5) monoclonal antibody and in ␤ 3 -null (glycoprotein IIb/IIIa-deficient) mice (Vega-Ostertag M, et al: unpublished observations).…”
Section: Discussionmentioning
confidence: 89%
“…Studies from our group have also shown that affinity-purified anticardiolipin antibodies (aCL) from patients with APS, but not from patients with syphilis, enhanced activation of platelets treated with suboptimal doses of ADP, thrombin, or collagen (7). In a recent study by our group, platelets pretreated with suboptimal doses of thrombin receptor agonist peptide (TRAP) and aPL expressed enhanced levels of activated glycoprotein IIb/ IIIa, indicating platelet activation (8). In another study, rabbit aCL were shown to enhance collagen-induced platelet activation (9).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Nonetheless, the pathogenic mechanisms of aPL seem to be heterogeneous and far from being completely understood (9). Among the mechanisms suggested to explain the prothrombotic activity of aPL are the direct inhibition of the activated protein C pathway (10), abnormalities in platelet function (11,12), up-regulation of the tissue factor pathway (13), and activation of endothelial cells (ECs) (14).…”
Section: Conclusion These Findings Indicate That Fluvastatin Signifimentioning
confidence: 99%
“…This assay depends only on primary hemostasis and thus is considered the classic test for the assessment of platelet function. Strong evidence of aPLinduced platelet activation is the enhanced expression of platelet membrane glycoproteins, particularly GPIIb-IIIa (fibrinogen receptor, critical in platelet aggregation) and GPIIIa [ 80 ]. More recently, Pierangeli et al showed that in mice with genetic deletion of GPIIb-IIIa, passive immunization with aPL did not increase clot formation [ 81 ].…”
Section: A S E C O N D I N D I C a T I O N O F I M P A I R E D P L A mentioning
confidence: 99%